2021
DOI: 10.1002/hyp.14033
|View full text |Cite
|
Sign up to set email alerts
|

Improved understanding of dynamic water and mass budgets of high‐alpine karst systems obtained from studying a well‐defined catchment area

Abstract: Large areas of Europe, especially in the Alps, are covered by carbonate rocks and in many alpine regions, karst springs are important sources for drinking water supply.Because of their high variability and heterogeneity, the understanding of the hydrogeological functioning of karst aquifers is of particular importance for their protection and utilisation. Climate change and heavy rainfall events are major challenges in managing alpine karst aquifers which possess an enormous potential for future drinking water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Q M C < 0). Such flow exchanges between capacitive and transmissive part of karst aquifers has been evidenced using KarstMod on other karst environment (Sivelle et al, 2019;Duran et al, 2020;Frank et al, 2021;Labat et al, 2022).…”
Section: It Is Ofmentioning
confidence: 87%
See 1 more Smart Citation
“…Q M C < 0). Such flow exchanges between capacitive and transmissive part of karst aquifers has been evidenced using KarstMod on other karst environment (Sivelle et al, 2019;Duran et al, 2020;Frank et al, 2021;Labat et al, 2022).…”
Section: It Is Ofmentioning
confidence: 87%
“…In order to address these issues, different modeling approaches have been developed (Jeannin et al, 2021) such as, among others, fully-distributed models (Chen and Goldscheider, 2014), semi-distributed models (Doummar et al, 2012;Dubois et al, 2020;Ollivier et al, 2020), and lumped parameter models (Mazzilli et al, 2019) including semi-distributed recharge (Bittner et al, 2018;Sivelle et al, 2022a). Among these, lumped parameter models are recognized as major tools to explore the ability of conceptual representations to explain observations in karst systems (Poulain et al, 2018;Sivelle et al, 2019;Duran et al, 2020;Frank et al, 2021) and for managing karst groundwater resources (Sivelle and Jourde, 2020;Sivelle et al, 2021;Labat et al, 2022;Cousquer and Jourde, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We aim to propose a hydrogeological model based on the KarstMod modeling platform [10], which can be modulated to simulate discharge at the outlet and to quantify the internal flows between the different compartments of the model and can be applied on various karst catchments [11][12][13][14]. KarstMod is developed by the Service National d'Observation du Karst (SNO Karst-INSU/CNRS).…”
Section: Lumped Parameter Modelingmentioning
confidence: 99%
“…Lumped parameter models are based on different system conceptualizations (e.g., Chen and Goldscheider, 2014;Cinkus et al, 2023b;Fleury et al, 2009;Jukić and Denić-Jukić, 2009;Mazzilli et al, 2019;Rimmer and Salingar, 2006;Tritz et al, 2011), as well as neural network approaches (e.g., Afzaal et al, 2020;Cinkus et al, 2023b;Kratzert et al, 2018;Renard and Bertrand, 2017;Wunsch et al, 2022). A common, significant feature encountered in karst systems -which is difficult to capture in models -is the interplay of rapid and slow flow which manifests as longtailed measurements of both discharge rates (e.g., Frank et al, 2021) and chemical tracer concentrations (e.g., Goeppert et al, 2020) observed at karst springs.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the CTRW framework, which has been developed to model anomalous chemical transport, is utilized to quantify long-tailing of water flow in karst systems. In this context, data from the Disnergschroef alpine study site in Vorarlberg, Austria are revisited (Frank et al, 2021). This high-alpine karst system has been thoroughly studied and offers a well-defined spatial catchment.…”
Section: Introductionmentioning
confidence: 99%